Can economic development be a driver of food system sustainability? Empirical evidence from a global sustainability index and a multi-country analysis - Béné, Christophe; Fanzo, Jessica; Achicanoy Estrella, Harold Armando; Lundy, Mark M. (2022)
Despite representing a growing element of the international community’s discourse, the sustainability of food systems and the challenge of its empirical measurement are still highly debated. In this paper, we propose to address this gap by computing a global food system sustainability index which we then use in a cross-country analysis covering 94 countries in low-, middle- and high-income regions. The analysis reveals a strong non-linear but positive correlation between the food system sustainability index and countries’ individual GDP per capita. This relationship suggests some possible degree of endogeneity between food system sustainability and economic development. We then use the Shared Socioeconomic Pathways framework and Individual Conditional Expectations modeling techniques to explore how the sustainability of food systems is projected to evolve in the future as countries move up the economic development ladder. The projections indicate that for lower income countries, the change is usually more significant than for higher income countries. The analysis also reveals that the different dimensions of sustainability will not all contribute equally to future improvements in food system sustainability. In particular, investments targeting social and food security & nutrition dimensions are projected to have a greater effect on the sustainability of food systems than investment/interventions aiming at the environment or economic domains. For countries located at the lower end of the economic development spectrum, this would imply that, even with limited resources, policy-makers could substantially improve the sustainability of countries’ food systems by prioritizing (sub)national policies and interventions focused on social and food security & nutrition domains.